From incidental exposure to intentional avoidance: Psychological reactance to political communication during the 2017 German national election campaign. (March 2021) - Marcinkowski, Frank; Došenović, Pero
This article deals with potential effects of incidental online exposure to political information (IOEP) on the German electorate during the 2017 national election campaign. We argue that the difference in currently unexpected and generally unwanted exposure to political online communication is crucial to the study of IOEP effects. While the former might result in "passive learning, " we hypothesize that–based on psychological reactance theory–the latter may be linked to defensive reactions with undesirable consequences among those who already are alienated from politics. Using cross-sectional data from an online survey among 1100 eligible voters, we can demonstrate that IOEP correlates with reactance in substantial segments. The study's results are indicating, that the viral character of online campaigning may lead to the opposite of what was intended: voters are not only "trapped, " but might be repelled instead. Further empirical elaboration dealing with causal assumptions is encouraged.